Resistance to Religious Moderation in Indonesian’s Lower to Middle-Class Communities - Mahmudah, Siti; Alamsyah, Alamsyah; Firdawaty, Linda; Yuliatin, Yuliatin; Yanti, Illy; Asnawi, Habib Shulton (SCAD Independent, 2025)
Lower-to-middle-class communities in Indonesia continue to exhibit resistance to religious moderation, frequently perceiving it as a foreign concept influenced by Western ideologies. This misconception persists even though religious moderation is deeply rooted in Islamic tradition and represents neither a new religion nor a secular invention. Such resistance often manifests through overt, semi-covert, and covert strategies, reflecting varying levels of opposition ranging from open rejection to more subtle forms of disengagement. This study employed a qualitative approach, drawing on data from online media platforms to analyze patterns of resistance and their underlying causes. The findings revealed that resistance was frequently driven by misinformation, distrust of government-led initiatives, and a limited understanding of the historical and theological foundations of religious moderation. These attitudes fostered intolerance and social fragmentation, posing a serious threat to national resilience, democratic values, and social harmony. Furthermore, the study emphasized that addressing resistance required not only educational interventions but also inclusive policymaking that bridged the gap between state narratives and grassroots religious experiences. The research offers crucial insights for policymakers and educators in developing culturally sensitive and community-based strategies to promote religious moderation and counteract the growing tide of intolerance in diverse socio-religious contexts across Indonesia.